Mitochondria Are Dynamically Transferring Between Human Neural Cells and Alexander Disease-Associated GFAP Mutations Impair the Astrocytic Transfer - Gao, Longfei; Zhang, Zhen; Lu, Jing; Pei, Gang (Frontiers in Cellular Neuroscience, 2019)
Mitochondria are the critical organelles for energy metabolism and cell survival in eukaryotic cells. Recent studies demonstrated that mitochondria can intercellularly transfer between mammalian cells. In neural cells, astrocytes transfer mitochondria into neurons in a CD38-dependent manner. Here, using co-culture system of neural cell lines, primary neural cells, and human pluripotent stem cell (hPSC)-derived neural cells, we further revealed that mitochondria dynamically transferred between astrocytes and also from neuronal cells into astrocytes, to which CD38/cADPR signaling and mitochondrial Rho GTPases (MIRO1 and MIRO2) contributed. The transfer consequently elevated mitochondrial membrane potential in the recipient cells. By introducing Alexander disease (AxD)-associated hotspot mutations (R79C, R239C) into GFAP gene of hPSCs and subsequently inducing astrocyte differentiation, we found that GFAP mutations impaired mitochondrial transfer from astrocytes and reduced astrocytic CD38 expression. Thus, our study suggested that mitochondria dynamically transferred between neural cells and revealed that AxD-causing mutations disrupted the astrocytic transfer, providing a potential pathogenic mechanism in AxD.